STATISTICAL ANALYSIS OF MUNICIPAL SOLID WASTE GRAVIMETRIC COMPOSITION AND HUMAN DEVELOPMENT INDEX FOR SAO PAULO STATE MUNICIPALITIES - Rodrigues Spinola, Gabriela Monteiro [UNESP]; Nascimento, Victor Fernandes; Andrade, Pedro Ribeiro; Balbuad Ometto, Jean Pierre (Univ Federal Goias, Dept Geografia, 2019)
The recent and unplanned population growth of humanity is directly associated to increase the municipal solid waste (MSW). The great challenge in Brazil is proper manage MSW, once this topic is little studied and there are few investments in the sector. This study aims to correlate the Human Development Index (HDI) and the organic matter described in the municipal solid waste plans (MSWP) for the Sao Paulo state' cities. To conduct the study, we used statistical and mathematical analyzes. The results showed that from 645 municipalities in the state, only a little more than half presented their MSWP. However, only 163 were found online and just 78, representing 12% of the total municipalities, presented gravimetric composition data on their MSWP. In addition, due to data scarcity, the statistical analysis did not present a linear and symmetric relationship between the variables. Concluding that for the municipalities of Sao Paulo state there is no strong association between the organic matter present in MSW and the HDI.
Keywords: Organic Matter; HDI; MSW generation